The Influence of Islamic Religious Education in Family and School Religious Culture on Students' Religious Discipline - Haidir Haidir; Mardianto Mardianto; Titik Ningsih; Tuti Ernawati; Wahyu Sakban (STAI Hubbulwathan Duri, 2023)
The rise of moral decline (multi-dimensional crisis) and generally also occurs among students, makes Islamic Education (PAI) considered unsuccessful in embodying its universal values. This study aims to determine whether Islamic religious education in the family affects students' religious discipline, and whether the religious culture of the school influences students' religious discipline. This study uses a correlational descriptive quantitative approach. The results showed that each independent variable and dependent variable had a positive correlation and a significant influence, where Islamic religious education in the family was 0.456, and the religious culture of the school was 0.373, which had an effect on students' religious discipline. Meanwhile, together there is a significant relationship between Islamic religious education in the family and the religious culture of the school, which is marked by R-value of 0.495 and R2 of 0.245. This means that the percentage of the influence of the independent variable (Islamic religious education in the family and school religious culture) on the dependent variable (students' religious discipline) is 24.5%, which affects students' religious discipline.